Relationship between serum NDRG3 and papillary thyroid carcinoma - Wang, Jiahao; Wang, Jun; Quan, Jinxing; Liu, Juxiang; Tian, Limin; Dong, Changhong (Frontiers in Endocrinology, 2022)
Background: In recent years, Papillary thyroid carcinoma is considered to be one of the fastest increaseing cancer. NDRG family member 3 ( NDRG3) has been proposed as a molecular marker of tumor, and is expected to be used in clinic. Methods: Enzyme-linked immunosorbent assay was used to detect the serum NDRG3 expression in 81 Papillary thyroid carcinoma cases, 75 benign thyroid nodules cases and 77 healthy control cases, respectively. Electrochemiluminescence method was applied to measure the levels of triiodothyronine, tetraiodothyronine, thyrotropin, thyroglobulin antibody and thyroid peroxidase antibody. Immunohistochemical staining was used to detect the expression of NDRG3 in Papillary thyroid carcinoma, benign thyroid nodules and normal tissues adjacent to cancer. Results: The expression of serum triiodothyronine, tetraiodothyronine, thyrotropin, thyroglobulin antibody and thyroid peroxidase antibody and NDRG3 were significantly different among benign thyroid nodules, Papillary thyroid carcinoma cases and healthy control groups (P <0.001). Only the expression of serum NDRG3 was significantly different between benign thyroid nodules) and Papillary thyroid carcinoma groups (P <0.001). Immunohistochemistry showed that NDRG3 was expressed in all three groups, the lowest in Papillary thyroid carcinoma, the second in benign thyroid nodules, and the highest in normal tissues adjacent to cancer. Logistic regression analysis showed that serum NDRG3 was an independent protective factor for Papillary thyroid carcinoma (OR =0.964, 95%CI =0.953 to 0.974, P <0.001). The ROC curve of non-Papillary thyroid carcinoma diagnosed by serum NDRG3 showed the optimal cut-off value of 481.38 pg/ml, sensitivity of 72.4%, specificity of 90.1%, and the maximum area under the curve (AUC =0.902, 95%CI =0.863 to 0.940, P <0.001). The ROC curve of benign thyroid nodules diagnosed by serum NDRG3 showed the optimal critical value of 459.28 pg/ml, sensitivity of 81.3%, and specificity of 74.1% (AUC =0.863, 95%CI =0.808 to 0.919, P <0.001). The expression level of serum NDRG3 was significantly correlated with extrathyroid extensionand (P =0.007) and lymphatic metastasis of Papillary thyroid carcinoma (P =0.019). Conclusions: The decrease of NDRG3 expression can not only differential diagnosis benign thyroid nodules and Papillary thyroid carcinoma, but also serve as a molecular marker for the diagnosis of Papillary thyroid carcinoma.